2008
DOI: 10.1111/j.1469-8986.2008.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia diagnosis and anterior hippocampal volume make separate contributions to sensory gating

Abstract: Impaired P50 gating is thought to reflect a core deficit in schizophrenia, but the relevant neural network is not well understood. The present study used EEG and MEG to assess sensory gating and volumetric MRI to measure hippocampal volume to investigate relationships between them in 22 normal controls and 22 patients with schizophrenia. In the schizophrenia group, anterior but not posterior hippocampal volume was smaller, and both the P50 and M50 gating ratios were larger (worse) than in controls. Independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Here, we observed the responses to syntactic violations more anterior in the temporal cortex compared to the other violations and the AC reference. Previously, the neural sources of the P50/M50 have been localized to the auditory cortex (Mäkelä et al, 1994;Huotilainen et al, 1998;Thoma et al, 2003Thoma et al, , 2008. While this also holds true for sentences including an ITD change in the current study and for the very early syntax effect found by B.…”
Section: Very Early Effects (40-90 Ms)mentioning
confidence: 56%
“…Here, we observed the responses to syntactic violations more anterior in the temporal cortex compared to the other violations and the AC reference. Previously, the neural sources of the P50/M50 have been localized to the auditory cortex (Mäkelä et al, 1994;Huotilainen et al, 1998;Thoma et al, 2003Thoma et al, , 2008. While this also holds true for sentences including an ITD change in the current study and for the very early syntax effect found by B.…”
Section: Very Early Effects (40-90 Ms)mentioning
confidence: 56%
“…The magnetic responses were digitally sampled at a rate of 1000 Hz. In order to keep subjects alert and to prevent them from paying attention to the auditory stimuli, we instructed them to watch a silent cartoon movie during the recordings (Thoma et al, 2008;Weisser et al, 2001).…”
Section: Meg Recordingmentioning
confidence: 99%
“…In rat brains, the response of hippocampal pyramidal interneurons, to the second stimulus was found to be almost completely suppressed above all in the CA3 region, indicating that the hippocampus might be an essential mediator of sensory gating (Bickford-Wimer et al, 1990;Freedman et al, 1996). In studies employing magnetencephalography (MEG), a method with high spatial resolution, the M50 was localized in the auditory cortex of the superior temporal gyrus but also to several sources in the frontal lobes (Garcia-Rill et al, 2008;Thoma et al, 2008;Weiland et al, 2008).…”
Section: Introductionmentioning
confidence: 96%